2012
DOI: 10.1111/acel.12009
|View full text |Cite
|
Sign up to set email alerts
|

Tyr682 in the Aβ‐precursor protein intracellular domain regulates synaptic connectivity, cholinergic function, and cognitive performance

Abstract: SUMMARY Processing of Aβ-precursor protein (APP) plays an important role in Alzheimer’s disease (AD) pathogenesis. The APP intracellular domain contains residues important in regulating APP function and processing, in particular the 682YENPTY687 motif. To dissect the functions of this sequence in vivo, we created an APP knock-in allele mutating Y682 to Gly (APPYG/YG mice). This mutation alters processing of APP and TrkA signaling, and leads to postnatal lethality and neuromuscular synapse defects when expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Previous studies have shown that transgenic mice lacking the APP–TrkA interaction demonstrate forebrain damage and cognitive deficits (Matrone et al ., ). Based on the effect of APP phosphorylation on APP–TrkA binding, the APP–TrkA interaction was investigated in the AD human brain where elevated APP pT668 levels have been reported (Lee et al ., ; Chang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that transgenic mice lacking the APP–TrkA interaction demonstrate forebrain damage and cognitive deficits (Matrone et al ., ). Based on the effect of APP phosphorylation on APP–TrkA binding, the APP–TrkA interaction was investigated in the AD human brain where elevated APP pT668 levels have been reported (Lee et al ., ; Chang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, observations from the KI mice suggested that the primary function of APP resides in the sAPPα extracellular fragment, as described earlier and that much of the CTF, including the YENPTY domain, is dispensable. In this context, it is quite surprising that a mouse with a targeted APP Y682G knockin mutation, where the first tyrosine residue of the YENPTY motif was substituted by glycine, exhibited developmental defects in the absence of Aβ deposition and accumulation [11, 80]. This would not be predicted given the mild phenotypes seen in mice where the C-terminus of APP was deleted.…”
Section: The –Yenpty– Domain: Beyond Endocytosismentioning
confidence: 99%
“…Tyr682 and Tyr687 are the only APP residues that are phosphorylated in vitro . Tyr682 phosphorylation seems to be critical for APP signaling and activity because of its ability to profoundly regulate the APP interaction according to its phosphorylation state. Interestingly, the GY 682 ENPTY 687 motif is 100% conserved from C. elegans to humans (Fig.…”
Section: Introductionmentioning
confidence: 99%